Surface Modification on OHNS Steel Using Cu-CrB2 Green Compact Electrode in EDM. (2018) - Kumar, P. Mathan; Sivakumar, K.; Jayakumar, N.
Abstract: Generally Electrical Discharge Machining (EDM) is used in making dies in precision industries. In recent days EDM is used to modify the machined surface using powder metallurgy green compact electrode. In this paper an attempt has been made to fabricate copper-chromium di boride (Cu-CrB2 ) electrode to modify the surface of OHNS material. The experiment was designed by using central composite design. Chromium di boride percentage, pulse current and pulse on time were selected as process parameters. Material Transfer Rate (MTR) and Surface Roughness (SR) were selected as output response. The effect of each parameter on MTR and SR was addressed using ANOVA technique. Second order regression equation was developed for each response. The machined surface was analysed by optical microscopy technique. From the analysis, it was established that desired deposition of hard composite layer were found on work piece.